Energy Efficiency to Improve Network Life Time Using Particle Swarm Optimization Algorithm - Kannadhasan, S.; Deepa, S.; Shanmuganantham, M. (EAI Endorsed Transactions on Context-aware Systems and Applications, 2020)
Remote Sensor Networks (WSNs) have a developing innovation for different applications in reconnaissance, condition, natural surroundings observing, medicinal services and fiasco administration. It has monitor through environment by using sensing device that means of physical properties. WSN is a network that can transmit and receive through the wireless medium by using the sensor devices for various nodes. There are various base stations to control final destination of data from one place to other place. It includes the dense ad-hoc deployment, dynamic topology, spatial distribution, and Network topology, Graph Theory with constraint the bandwidth, energy life time and memory. Based on the problem size increases, it can require as various efforts by using the optimization techniques. This paper is to distinguish the deficiencies in Wireless Sensor Networks the hubs have transmitted starting with one place then onto the next by utilizing the particle swarm enhancement. PSO calculation is contrasted and the different calculations PCA, Neural system and OPAST. Based on the algorithm, the performance analysis is done on specificity, fault detection and fault coverage. The simulation result shows the energy life time, throughput, packet delivery ratio produces good performance when compared to the other algorithms.
Keywords: WSN; PSO; Throughput; Analysis of Node and Energy Efficiency